2012
DOI: 10.5137/1019-5149.jtn.7649-12.0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy for craniocerebral firearm injury

Abstract: AIm:The current study aims to explore the clinical characteristics of craniocerebral firearm injury and to improve the diagnosis and treatment of this condition. mAterIAl and methOds: Data from 56 patients with craniocerebral firearm injury were analyzed retrospectively for projectile types, traumatic conditions, and treatment approaches.results: 43 patients exhibited intracranial foreign body residence. Of them, 40 were subjected to complete foreign body removal and 2 to partial removal, leaving 1 without rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Some scholars believe that the metallic foreign bodies can’t to remove when they are located in deep vital structures, with small in size or has life-threatening by operation. However, for lead bullets and cranial fragment bodies, they should be removed completely because of their increased toxicity and chance of infection compared with other foreign bodies [ 23 ]. In addition, intracranial shrapnel or projectiles >5 mm in diameter need to be completely removed because they are prone to foreign body displacement and can cause local brain tissue hyperplasia inducing epilepsy or toxic effects on brain tissue (especially lead and aluminum bullets) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars believe that the metallic foreign bodies can’t to remove when they are located in deep vital structures, with small in size or has life-threatening by operation. However, for lead bullets and cranial fragment bodies, they should be removed completely because of their increased toxicity and chance of infection compared with other foreign bodies [ 23 ]. In addition, intracranial shrapnel or projectiles >5 mm in diameter need to be completely removed because they are prone to foreign body displacement and can cause local brain tissue hyperplasia inducing epilepsy or toxic effects on brain tissue (especially lead and aluminum bullets) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Paradot et al [7], Aarabi et al [5], and Wei et al [16] found respectively that the age (< 15 years vs > 16 years) of patients, the time between injury and admission (< 8 h vs > 8 h) were differently distributed in terms of outcomes. This may be explained by the difference of distribution of age and time from injury to the hospital between our study and theirs [5,16]. Literature has documented that patients victims of PCCI had most of the time a low GCS and unstable hemodynamic state [4,17,18].…”
Section: Clinical Presentations and Imagingmentioning
confidence: 99%